Evaluation Of Noise Pollutıon In Firat University Campus - Koçer, Nilüfer Nacar; Durmuş, Barbaros (Batman Üniversitesi, 2018)
Traffic noise is a growing environmental problem that highly affects the health of people. With the rapid increase in the number of motor vehicles, the traffic noise has become one of the main sources of pollution of urban environmental noise pollution that restrict the quality of the urban living environment. The main objective of this study is to determine the noise pollution on Elazığ city Firat University campus. For this purpose, noise measurements were carried out four times a day when traffic was intense. Noise measurements were made between 07:00 - 10:00 in the morning, 11.00 - 14.00 noon, 16:00 - 18:00 in the afternoon and 19:00 - 20:00 in the evening.  As a result of the study, the intersections where the noise level is highest and lowest in the university campus area have been determined.